Research on dispersion compensation using avalanche photodiode and pin photodiode. Issue 3 (17th December 2020) - Ma, Yanxia; Chen, Qinghui; Wang, Shuyan; Sharma, Shalini; Khanna, Shaweta
Abstract: With the growing demand for usage among Internet users, inventions related to increase in the capacity and bandwidth of transmission channels are more significant nowadays. This continuously growing demand can be fulfilled by using the optical fibre for transmission of signals instead of the wireless mode of transmission, due to the less non‐linearity present in the optical fibre. As every available mode has its own shortcomings so does the optical fibre. It suffers from dispersion and other linearities when long‐distance transmission is considered. Hence, the field of invention is associated with the compensation of dispersion in optical fibre communication at higher bit rates of 50–80 Gbps for longer distances of 120 km. After their compensation, comparison of two photodiodes, that is, pin diode and avalanche photodiode has been done at these distinct bit rates in order to achieve the best suited photodiode. After the complete analysis of simulations in terms of quality factor and bit error rate, it has been observed that at distinct bit rates of 50–80 Gbps, the simulation model using avalanche photodiode exhibits superior performance to that of the pin diode. The comparison results show that the performance of the avalanche photodiode is around 11% better than the pin diode.